1987
DOI: 10.1037/0022-3514.52.1.145
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocity of social exchange and social satisfaction among older women.

Abstract: Reciprocity is widely believed to be an important determinant of social satisfaction, yet relatively little research has examined reciprocity in ongoing primary relationships. In this study I investigated the association between reciprocity and older women's satisfaction with their social relationships. The sample consisted of 120 elderly widowed women. Analyses indicated that social exchange patterns that either overbenefited or underbenefited respondents were associated with greater loneliness. Reciprocity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
214
3
7

Year Published

1991
1991
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(236 citation statements)
references
References 47 publications
(55 reference statements)
12
214
3
7
Order By: Relevance
“…also indicates that the youngest respondents tend to provide more instrumental support than they receive, while the opposite is observed for the oldest. These findings are in contrast to those of earlier studies (Morgan et al, 1991, Rook, 1987 which reported overbenefitting by the elderly, that is, the elderly gave more than they received. Figure 8.4 uses the same data as Figure 8.3, but the presentation is different.…”
Section: Differences In Intensity Of Supportcontrasting
confidence: 56%
“…also indicates that the youngest respondents tend to provide more instrumental support than they receive, while the opposite is observed for the oldest. These findings are in contrast to those of earlier studies (Morgan et al, 1991, Rook, 1987 which reported overbenefitting by the elderly, that is, the elderly gave more than they received. Figure 8.4 uses the same data as Figure 8.3, but the presentation is different.…”
Section: Differences In Intensity Of Supportcontrasting
confidence: 56%
“…With the sources of support failing to explain the age differences on the associations between received social support and positive/NA found, several alternative theoretical perspectives may account for the data: first, a potential underlying mechanism for age differences in the association between emotional support and well-being is an age-related difference in reciprocity of social exchanges (Rook 1987). Equity theory posits that a perceived imbalance of social exchanges (e.g., providing and receiving emotional support) in either direction is detrimental for an individual's well-being (Walster et al 1978).…”
Section: Discussionmentioning
confidence: 99%
“…These networks have many structural characteristics: size, density, composition (i.e., what categories of people are most represented), and length of relationships (Wellman, 1981). Social ties within our networks serve many vital functions that include providing access to needed resources, support, control, and companionship (see Rook, 1987aRook, , 1987b. But the interpersonal characteristics of our social networks may also include social constraints and=or conflict (e.g., Lepore, 1992;Lepore, Silver, Wortman, & Wayment, 1996).…”
Section: Social Network Characteristicsmentioning
confidence: 99%